Liquid biopsy in lung cancer: tertiary prevention potential. (30th September 2020) - Rubba, F; Pepe, F; Martello, R; Egidio, R; De Pascale, T; Loperto, I; Iervolino, A; Malapelle, U; Triassi, M; Troncone, G
Abstract: Background: In the era of personalized therapy liquid biopsy is considered an important diagnostic tool in the clinical management of cancer patients. Tissue specimen represents "gold standard" for molecular evaluation of specific gene targets alterations that lead cancer patients to benefit of a "tailed therapy" based on molecular features of the tumor. This innovative source of nucleic acids was introduced in clinical setting only for NSCLC patients to test Epidermal Grow Factor Receptor (EGFR) mutations when tissue is not available or to monitor acquired resistance mutation after a first line of treatment. The study aimed at assessing the diagnostic potential of liquid biopsy in balanced tertiary screening modeling. Methods: The cases relating to 5 years of activity regarding to molecular diagnostics performed on liquid biopsy specimens in the Predictive Diagnostic laboratory of AOU Federico II were reviewed. Laboratory data were collected in SPSS. Non parametric analysis were performed in order to test the differences between patients WILD TYPE or not. A multivariate logistic model was performed in order to assess the effect of mutation, age and sex, on the tumor progression. The results of the revision concern 515 total cases (almost of all plasma or peripheral blood) allowed to evaluate the liquid biopsies for women and men. The average age of the Patients is 66.3 years, and the 25 percentile is 59 years. Results: The cases are 221 basal and 294 by progression. The cases with mutation, as expected, have an OR 4, 15 compared to the basal to have a tumor progression (95% IC: 2, 7 - 6, 3) regardless of sex and age. The mutations detected were 131 from different types of pulmonary carcinomas. Conclusions: Working on case data, specifying the characteristics of the Patients with mutations will drive a further estimate in tertiary prevention screening designs. Key messages: In the last five years, the liquid biopsy has been used for different purposes in oncology. To specify the characteristics of the Patients with mutations will drive a further estimate in tertiary prevention screening designs.